Temperature and strain rate effect on tensile properties of 9Cr–1·8W–0·5Mo–VNb steel. (April 2015) - Sakthivel, T.; Laha, K.; Parameswaran, P.; Paneer Selvi, S.; Mathew, M. D.
Abstract : Tensile tests have been carried out on 9Cr–1·8W–0·5Mo–VNb steel (grade 92) over wide ranges of temperature (300–923 K) and strain rate (3×10 −3 –3×10 −5 s −1 ). The tensile strength of the steel decreased slowly with temperature at relatively lower temperature range, whereas rapidly in the higher temperature range with a plateau in the intermediate temperature range. The decrease in strain rate decreased the tensile strength of the steel both at lower and higher temperature ranges. Elongation to fracture and reduction in area increased with increase in temperatures and decrease in strain rate at higher temperature regime with a plateau in the intermediate temperature regime. The ductile mode of tensile failure has been observed in the investigated temperatures and strain rates. The plateau in the variation of tensile strength with temperature, the negative strain rate sensitivity of tensile strength and minimum in ductility of the steel in the intermediate temperature range are considered as a consequence of dynamic strain ageing. The rapid decrease in tensile strengths and increase in ductility at high temperatures have been attributed to the dynamic recovery.